From action to legislation: challenges and enhancements of the regulatory frameworks concerning China’s blue carbon sink trading - Chuanliang Wang; Zhaoxin Liu; Aiping Wang (Frontiers in Marine Science, 2026)
The Ecological Environment Code of the People’s Republic of China has incorporated ecosystem carbon sinks into the legal system, yet there remains a lack of specialized legislation for blue carbon sink trading, with obvious normative limitations in its supervision and management. This research mainly adopts a combined research method integrating normative analysis, legal doctrine analysis, and qualitative policy text analysis. It systematically reviews China’s existing laws and policies related to carbon sinks and analyzes the institutional status of blue carbon sink trading supervision and management from three dimensions: subject, content, and liability. The study identifies three core problems in the current supervision system: vague and nominal allocation of powers and responsibilities among regulatory subjects with prominent functional overlaps; missing and imbalanced transaction process rules lacking systematic planning; and a weak and formalistic accountability mechanism with unclear responsibility boundaries. To enhance the regulatory frameworks, at least three areas should be addressed: first, clarify the rules of regulatory entities, and build a complementary, professional and efficient supervision mechanism. Second, enhance rules of the regulatory bodies, along with rules for the declaration and registration of blue carbon sink projects. Finally, strengthen rules of legal liabilities for the supervision and management of blue carbon sink trading, clarifying the provisions on the legal liabilities of relevant entities, and enhancing the effectiveness of legal liability pursuit.